Kothmale Community Radio Interorg Project: True Community Radio or Feel-Good Propaganda? - Harvey-Carter, Liz (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The Kothmale Community Radio and Interorg project in Sri Lanka has been hailed as an example of how a community radio initiative should function in a developing nation. However, there is some question about whether the Kothmale Community Interorg Project is a true community radio initiative that empowers local communities to access ICT services and to participate freely and equally or another “feel-good” project controlled by successive, repressive Sri-Lankan governments and international partners, as alleged by its critics? After two decades of operation, the evidence shows that the Kothmale project is a cautionary tale about what can go wrong when an ICT project is not strongly promoted as a community-based enterprise. The biggest lesson that the Kothmale model can teach us is that control of community radio must be in the hands of the community exclusively if it is to succeed.